Industrial Relations and Technological Change : Swedish Trade Union and Employers’ Views and Agreements - Malles, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
« An interest organization which limits itself to guarding existing group interests risks becoming petrified in tradition and losing all influence over developments. On the other hand, if an organization accepts change and is able to integrate the group interest within the overall process of development, the aims of the organization will he accepted as progressive and the organization will have the possibility of actively influencing the course of the future. »